The socioeconomic gradient in Tuberculosis mortality in Mexico (2004-2008) - Meza-Palmeros, José Alejandro (2013)
Objective: To analyze the relationship between mortality from tuberculosis (TB) and various indicators of social backwardness (under food poverty line, occupation, percentage of indigenous language speakers) in Mexico during 2004-2008. Methods: We created a database of registered deaths from TB in the country from 2004 to 2008 which included: municipality, place of residence and occupation by economic sectors (primary, secondary, tertiary) and by the condition of being employed/unemployed of the deceased; information related to the degree of social backwardness by locality (percentage of indigenous language speakers) and municipality (percentage of population living under the food poverty line). Then, we estimated the rates of TB mortality according to the variables mentioned above. Statistical analysis was performed using chi-square tests and linear regression.Results: We found that TB mortality follows a socioeconomic gradient that is expressed through a statistically significant association between TB mortality and the indicators analyzed (degree of social backwardness, percentage of indigenous speakers by locality, economic sector and occupation, and to be employed /unemployed). Conclusions: TB mortality in Mexico seems to focus on the socially vulnerable population, so it is necessary to pay special attention to the social determinants of TB in its prevention and control strategies.